Cartulary of the Grisons – Bündner Urkundenbuch (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The Cartulary of the Grisons (Bündner Urkundenbuch) contains in eight volumes all known medieval charters and deeds concerning the area of the Grisons, from the beginning of the diocese of Chur around 400 A.D. until the year 1400. This edition presents more than >000 documents of different origin, published in extenso or in the form of abstracts, and stored mainly in Swiss, German, Italian, and Austrian archives. It is an important basis for the historiography of the Grisons, including border regions such as the Val Venosta, Tyrol, Voralberg, St. Gall, Zurich, Valchiavenna, Valtellina and the areas surrounding the cities of Como and Milan.
Keywords: Cartulary; edition of sources; medieval charters; history of the Grisons